Subjective Norms and Perceived Ease of Use Driving Healthcare Information System Behaviour - Sulistiowati Sulistiowati; Jusak Jusak; Dyan Angesti; Erwin Sutomo; Titik Lusiani (Jurnal Manajemen Kesehatan Yayasan RS.Dr. Soetomo, 2026)
This study investigates the adoption of Hospital Information Systems (HIS) through an extended Technology Acceptance Model (TAM), uniquely positioning user satisfaction as a mediator within a mandatory clinical setting. While traditional models emphasize satisfaction as a prerequisite for success, this research reveals a paradoxical shift at RSU Dr. Suyudi, where HIS usage is compulsory. Analyzing data through PLS-SEM, the results demonstrate that User Satisfaction plays a non-significant role in bridging system perceptions and actual usage behavior. Instead, the structural path is heavily dominated by Subjective Norms and Professional Image, which significantly drive Perceived Usefulness. Furthermore, the influence of Perceived Ease of Use and Subjective Norms on Usage Behavior remains robust. These findings indicate that in the hospital setting, professional norms and system simplicity carry much more weight than individual affective satisfaction. Theoretically, this study challenges the necessity of the satisfaction construct in mandatory digital health frameworks. Managerially, hospital administrators should pivot from superficial satisfaction metrics toward strengthening digital work cultures and streamlining user interfaces. By prioritizing professional prestige and operational ease, organizations can ensure more effective system integration in high-stakes clinical environments.